Menjadi Gereja Kecil: Peran Sentral dan Strategis Keluarga dalam Membangun Fondasi Iman Anak - Adelbertus Beato Yulandi; Irenius Bima Abdiono; Asran Asran (Publisher STPKat, 2025)
This study explores the central and strategic role of families in shaping the faith foundation of their children by viewing the family as a “little church”. This concept emphasizes the importance of the family environment in shaping children's religious beliefs and practices. The purpose of this study is to ultimately discover what are the roles of families in shaping and building the foundation of children's faith. The study also aims for families to have an overview of their existence in a “small church”. This study uses a qualitative methodology by focusing on analyzing the phenomenon of today's family from the perspective of the Ecclesiastical Document Series No. 30 FAMILIARIS CONSORTIO. Through a qualitative approach, we investigated how families play a major role in strengthening the faith of their children through various daily religious practices, Bible study, prayer, and participation in joint religious activities. Our findings highlight the importance of parents' role as faith models and spiritual educators for their children, as well as the close relationship between family interactions and the formation of children's faith foundation. The practical implications of this study emphasize the need for church support for families in strengthening their central role in guiding children's faith development.